Alkyd based water-reducible anticorrosive paints and their antifungal potential - Martinez, Marcos (2021)
Concerns about ozone layer, contamination, fossils resources and health, has banned or restricted the use of traditionally organic solvents in paints. As a consequence, new resins that employed water as main solvent are being studied. Among these resins, alkyds are the most studied one as they can also be synthesised from natural vegetable sources, making them more acceptable. The aim of this paper was to study the anticorrosive behaviour of alkyd / polysaccharide paints containing zinc phosphate or zinc aluminum phosphate as main pigment and their performance against fungal growth. Two different PVC (pigment volume concentration) were studied. Painted panels were studied by exposition to salt spray and humidity chambers, where rusting and blistering degrees were evaluated, and by electrochemical tests (corrosion potential measurements, ionic resistances determination, linear polarization curves and polarization resistances determination). Results showed that these type of paints can be used to protect steel and that the type of pigment and the PVC are important to the protection. Besides, good selection of both also prevents fungi growth in a high humid environment.